Does Foveal Hypoplasia Affect Emmetropization in Patients with Albinism? - Line Kessel; Christine Dahlgren Bohnsack Kjølholm; Joaquim Torner Jordana (MDPI AG, 2023)
(1) Background: The aim of the study was to describe refractive development from early childhood to adulthood in Danish patients with albinism and to evaluate the effect of foveal developmental stage on refractive development; (2) Methods: Patients with a clinical diagnosis of ocular or oculocutaneous albinism were invited for a refractive evaluation and comprehensive phenotyping including macular optical coherence tomography (OCT) scans. Foveal hypoplasia was graded based on OCT from 0 (normal) to 4 (absence of any signs of foveal specialization). Medical files were reviewed for historical refractive values in individual patients; (3) Results: Hyperopia (spherical equivalent refraction (SEQ) of ≥+1 Diopter (D)) was common in both children (81.3%) and adults (67.1%). The lower prevalence of hyperopia in adults was predominantly explained by increasing astigmatism with age. Emmetropization (>2D change from before 3 years to adolescence) was seen in 22.2%. There was no influence on foveal hypoplasia grade on the degree of refractive errors throughout life; (4) Conclusions: We found that emmetropization was uncommon in Danish patients with albinism and that the degree of foveal developmental stage did not influence emmetropization or the distribution of refractive errors. High degrees of hyperopia and astigmatism were common. These results indicate that fear of impeding emmetropization should not refrain the clinician from providing adequate correction for refractive errors in young children with albinism.